On the Influence of Selected Factors on the Public Image of the School Subject Geography - Hemmer, Ingrid; Hemmer, Michael; Miener, Kim Pascal (Journal of Geography Education, 2017)
The image of geography as a school subject is frequently under debate and highly relevant for the subjects future. The following article presents the results of a representative study, which surveyed the German populations images of the subject. The study focuses on the analysis of data with regard to influencing factors on these images. The factors analysed were age, gender, federal state, educational degree, presence of school-age children and contact with geographers. In this study, the respondents assigned an overall high relevance to the subject. The population rated the relevance for individuals significantly higher than a social relevance. Moreover, respondents are of the opinion that competences in the field of spatial orientation, the understanding of natural phenomena and the analysis of space are well promoted by teaching geography. In terms of geographic topics, the population considers the treatment of environmental issues by far the most important. On the basis of these analyses it can be stated that the above mentioned factors only have minor influence on the image of the subject. Worth mentioning are differences concerning the groups of federal states. In comparison it can be assessed, that eastern federal states predominantly display more positive data.